The effect of cryogenic cooling condition on surface defect when end milling carbon fibre reinforced polymers - Wee, Jenn Leong; KAMDANI, KAMARUDDIN (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Carbon fibre reinforced polymer is now a common material that used in airline and automotive industry due to light weight and high strength ratio of properties. CFRP is also known as material that hard to handle or machining. After the production of CFRP, it is required to go through secondary machining process in order to get desire parameter or shape. During machining CFRP process, there are defects such surface defects, delamination, induced damage and more which cause the machined CFRP rejected. The reason behind the rejected workpiece is the surface or properties of CFRP is possibly deteriorated. Therefore, in order to obtain a proper or desire workpiece, parameter such as tool geometry, cooling technique, fibre orientation and machining parameter is studied. The result able to conclude from the review papers is cryogenic cooling technique is one of the best methods in machining CFRP as cryogenic work mostly 20% to 30% effectively for the workpiece quality. Other than that, it is proven cryogenic cooling technique lengthen tool life and used less energy. Furthermore, machining parameter such cutting speed and feed rate able to improve the surface quality of the machined workpiece; with the usage 500mm/min of cutting speed and 0.03mm/rev feed rate with the usage of cryogenic cooling technique to end milling CFRP of 45˚ unidirectional fibre orientation able to improve the surface quality and properties. Lastly, the tool geometry and material are also important for better quality of machined workpiece and able to conclude that machining CFRP is about the combination of parameter for good machined workpiece.